2021
DOI: 10.7759/cureus.18772
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar Leiomyosarcoma in Pregnancy

Abstract: Vulvar leiomyosarcoma is a rare smooth muscle malignant neoplasm but it is the commonest type of vulvar sarcomas. It may mimic benign tumors and misdiagnosis could delay proper management. We report a case of a 38-year-old pregnant woman with leiomyosarcoma of the vulva. The patient presented to her primary general practitioner with a small vulvar mass that she had first noticed one year prior. The tumor was suspected to be benign Bartholin's cyst and treated with antibiotics. The patient declined improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In our case series, 66.7% of VLMS were initially misdiagnosed as a Bartholin’s gland abscess or cyst. When compared to the existing body of literature on VLMS, 7 of 11 cases were initially diagnosed as a Bartholin’s gland cyst or abscess (63.6%) ( Table 3 ) [ 33 , 34 , 37 , 38 , 45 , 46 , 49 ]. There was no information on the initial diagnosis in 15 of the 26 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, 66.7% of VLMS were initially misdiagnosed as a Bartholin’s gland abscess or cyst. When compared to the existing body of literature on VLMS, 7 of 11 cases were initially diagnosed as a Bartholin’s gland cyst or abscess (63.6%) ( Table 3 ) [ 33 , 34 , 37 , 38 , 45 , 46 , 49 ]. There was no information on the initial diagnosis in 15 of the 26 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Aljehani et al observed a frequency of menstrual irregularities in Saudi women of child bearing age after COVID-19 vaccination, mostly affecting the cycle duration and dysmenorrhea [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“… 35 LMS includes three subtypes: spindled, epithelioid, and myxoid. 36,37 There is a solitary mass, usually with a diameter of more than 5 cm, and circumscribed or infiltrative borders. The cut surface is soft or firm and fleshy white-tan-gray with variable hemorrhage, necrosis, and cystic change.…”
Section: Introductionmentioning
confidence: 99%